Minat Membaca Siswa Sekolah Menengah Pertama di Wilayah Pedalaman: Studi pada SMP Negeri 2 Donri-Donri Soppeng - Nugraha, Wandi; Sultan, Sultan; Haliq, Abdul (Nuances of Indonesian Language, 2024)
This research aims to (1) determine the level of reading interest of students at SMP 2 Donri-Donri Soppeng in rural areas; (2) find out the factors that influence students' interest in reading at SMP 2 Donri-Donri Soppeng in rural areas. The type of research used is Quantitative and Qualitative research with a descriptive approach. The data in this research uses quantitative data obtained from the results of a questionnaire filled in by all 87 students of Donri-Donri 2 Middle School and qualitative data obtained from interviews with the Principal, Teachers and Students. The data analysis technique for this research is quantitative and qualitative data analysis. Quantitative data analysis is used to obtain the level of reading interest, while qualitative data analysis is used to obtain factors that influence reading interest. The results of the research reveal that the level of reading interest of students at SMP Negeri 2 Donri-Donri in rural areas is still low and the factors that influence students' interest in reading at SMP Negeri 2 Donri-Donri are internal and external factors. Internal factors include gender and external factors include the availability of reading materials, school policies, digital media, and economic factors.